Identification of the Structure of Economical Statistical Data - Valkauskas, Romualdas (Ekonomika, 1997)
Data of economical statistics contains different structures. Economical and statistical analys of the changer of the structure of data is an important problem for science and for the practice of statistics. There exist two cases of indicators of the change of the structure: simple and general. The first case consists of absolute and relational indicators. On the basis of count lie simple methods. This case has no problem. The count of general indicators can be various. First of all. the changes of the structure are identical according to their measures of variation. The general measures of variation is the standard deviation. The formula of the average absolute deviation must be changed. Such an indicator is more exact than the standard deviation, reflecting change exactly. Another method of identifying the general change of the structure is to use procedures to detect the degree of change in the forecast project. Research procedures [hat detect the degree of change show that an indicator can be a coefficient of H. Theil. A formula of this indicator will be a model used to form another indicator. We suggest a formula to identify the general change structure that is reflected.